DEVELOPING A LOCAL CULTURE-BASED PICTURE STORYBOOK IN THE FORM OF FABLE FOR TEACHING ENGLISH FOR YOUNG LEARNERS - ., Putu Widya Savitri; ., Drs.Gede Batan,MA; ., Dra.Ni Made Ratminingsih, MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
This research was a research and development study which aimed at developing a local culture-based picture storybook entitled “Siap Selem”. Balinese local culture used is in a form of fable. It applied a framework proposed by Sugiono (2014). The data were collected from observation, interview and literature review in designing the product. The results are the picture storybook entitled “Siap Selem” obtains content validity (cv = 0.88), categorized as very high, while the quality is judged excellent with score 4.57, which each of the result was analyzed by using Gregory Formula and Likert Scale. Thus, it can be stated that the picture storybook developed is expected to be an appropriate supplementary reading for pleasure material for teaching English for TEYL (Teaching English to Young Learners).Kata Kunci : young learners, local culture, reading for pleasure, story, fable, picture book Penelitian ini merupakan studi penelitian dan pengembangan yang bertujuan untuk mengembangkan buku cerita bergambar yang berjudul “Siap Selem”. Budaya lokal yang digunanakan adalah Bali dalam bentuk fabel. Dalam mengembangkan buku cerita bergambar digunakan kerangka penelitian dan pengembangkan yang dikemukakan oleh Sugiyono (2014). Data yang berupa observasi, interview, dan kajian pustaka digunakan dalam membuat produk penelitian. Hasil penelitian adalah validasi isi (cv = 0.88) tergolong sangat tinggi, sedangkan qualitas dinilai sangat baik dengan nilai 4.57, dimana setiap hasil tersebut dianalisa dengan menggunakan Gregory Formula dan skala Likert. Jadi, dapat dinyatakan bahwa buku bergambar yang dikembangkan, diharapkan sesuai untuk pembelajaran Bahasa Inggris sebagai materi tambahan membaca untuk kesenangan dalam TEYL.keyword : Pelajar muda, budaya lokal, membaca untuk kesenangan, buku cerita, fael, buku bergambar